2023
DOI: 10.1088/1755-1315/1183/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Indirect organogenesis of Aceh patchouli leaf explants (Pogostemon cablin Benth) by in vitro

Abstract: The Aceh patchouli plant (Pogostemon cablin. Benth) is a plantation plant that produces essential oils with great potential, known as patchouli oil. The use of in vitro culture techniques on patchouli plants needs to be developed to meet the needs of patchouli seeds. This study aimed to analyze the effect of plant growth regulators (PGRs) cytokinins 6-Benzyl Amino Purine (BAP) and Thidiazuron (TDZ) and auxin 1-Naphthaleneacetic Acid (NAA) on the organogenesis ability of Aceh patchouli leaf explants var. Lhokse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Our research demonstrated that TDZ combined with NAA successfully achieved the differentiation of adventitious shoot buds, and the buds grew robustly. These findings align with previous studies on the differentiation of adventitious buds in Pogostemon cablin, Cotoneaster wilsonii and Allium hirtifolium [53][54][55]. In the study of Cotoneaster wilsonii, the effect of TDZ on adventitious bud differentiation was better than that of 6-BA [54].…”
Section: Discussionsupporting
confidence: 91%
“…Our research demonstrated that TDZ combined with NAA successfully achieved the differentiation of adventitious shoot buds, and the buds grew robustly. These findings align with previous studies on the differentiation of adventitious buds in Pogostemon cablin, Cotoneaster wilsonii and Allium hirtifolium [53][54][55]. In the study of Cotoneaster wilsonii, the effect of TDZ on adventitious bud differentiation was better than that of 6-BA [54].…”
Section: Discussionsupporting
confidence: 91%